The FBI Way : inside the Bureau's code of excellence - Figliuzzi, Frank (New York, NY : Custom House, 2021)
"The FBI's former head of counterintelligence delivers a field-tested playbook for unlocking individual and organizational excellence, based on the FBI's fiercely protected code of conduct and illustrated through dramatic stories from his own storied career"--
Introduction: hot wash -- Code -- Conservancy -- Clarity -- Consequences -- Compassion -- Credibility -- Consistency -- Epilogue: ops plan.
Includes index.
Keywords: United States. -- Federal Bureau of Investigation; Law enforcement -- United States -- Management -- Case studies; Professional ethics -- Case studies; Organizational behavior -- Case studies